2018
DOI: 10.1088/1748-9326/aab190
|View full text |Cite
|
Sign up to set email alerts
|

The southern African climate under 1.5 °C and 2 °C of global warming as simulated by CORDEX regional climate models

Abstract: Results from an 25 regional climate model simulations from the Coordinated Regional Downscaling Experiment Africa initiative are used to assess the projected changes in temperature and precipitation over southern Africa at two global warming levels (GWLs), namely 1.5 • C and 2.0 • C, relative to pre-industrial values, under the Representative Concentration Pathway 8.5. The results show a robust increase in temperature compared to the control period ranging from 0.5 • C-1.5 • C for the 1.5 • C GWL and from 1.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
109
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(124 citation statements)
references
References 41 publications
14
109
1
Order By: Relevance
“…Although Africa is one of the regions projected to be hard-hit by the brunt of climate change (Niang et al, 2014), similar studies on the impacts of 1.5 and 2°C of global warming have been relatively limited in comparison to other parts of the world. However, in the recent past, there have been studies that employed regional climate models driven by global models from phase five of the Coupled Model Intercomparison Project (CMIP5; Taylor et al, 2012) in investigating climate risks at 1.5°C and/or 2°C warming levels over Africa (Klutse et al, 2018;Maure et al, 2018;Nikulin et al, 2018;Osima et al, 2018;Pokam Mba et al, 2018). The collective finding from these studies is that the 0.5°C upsurge in global warming from 1.5°C leads to insignificant increases in precipitation in most parts, especially in the subtropics.…”
Section: Introductionmentioning
confidence: 99%
“…Although Africa is one of the regions projected to be hard-hit by the brunt of climate change (Niang et al, 2014), similar studies on the impacts of 1.5 and 2°C of global warming have been relatively limited in comparison to other parts of the world. However, in the recent past, there have been studies that employed regional climate models driven by global models from phase five of the Coupled Model Intercomparison Project (CMIP5; Taylor et al, 2012) in investigating climate risks at 1.5°C and/or 2°C warming levels over Africa (Klutse et al, 2018;Maure et al, 2018;Nikulin et al, 2018;Osima et al, 2018;Pokam Mba et al, 2018). The collective finding from these studies is that the 0.5°C upsurge in global warming from 1.5°C leads to insignificant increases in precipitation in most parts, especially in the subtropics.…”
Section: Introductionmentioning
confidence: 99%
“…However, GCMs have a weak point in resolution for reflecting the realistic impacts of local forcing with detailed topography or land use types Choi et al, 2016;Im et al, 2006Im et al, , 2007Im et al, , 2015Lee & Hong, 2014). Therefore, numerous dynamically downscaled climate change assessments at the target GWL based on the regional climate model (RCM) have actively been carried out in line with the Coordinated Regional Climate Downscaling Experiment (CORDEX) project: Donnelly et al (2017), Dosio and Fischer (2018), Jacob et al (2018), and Marx et al (2018) for the EURO-COREX domain;and, Nikulin et al (2018), Maúre et al (2018), Mba et al (2018), and Lennard et al (2018) over the CORDEX-Africa domain.…”
Section: Introductionmentioning
confidence: 99%
“…Schleussner et al (2016) found a 2% increase in the intensity of heavy rainfall between a 1.5 and 2.0 C globally and a 3% increase over South Asia. However, Rogelj et al (2015) warned that limiting the warming to below 1.5 C may require greater mitigation efforts and higher mitigation costs than keeping it at 2.0 C. Over Africa, some studies found higher impacts at 2.0 C GWL than at 1.5 C (Diedhiou et al, 2018;Klutse et al, 2018;Maúre et al, 2018;Mba et al, 2018;Nikulin et al, 2018;Osima et al, 2018;Weber et al, 2018;Tamoffo et al, 2019). For example, Weber et al (2018) found that rainfall intensity is likely to increase under a higher global warming scenario, especially over the sub-Saharan coastal regions.…”
mentioning
confidence: 99%
“…Both CORDEX and NEX datasets are freely available for regional climate change studies. However, while a few studies have discussed COR-DEX projections over southern Africa (e.g., Déqué et al, 2017;Maúre et al, 2018;Nikulin et al, 2018), thus far, no study has examined NEX projections over the subcontinent. For instance, analysing the CORDEX dataset at a 2.0 C warming level, Déqué et al (2017) projected fewer rain days but more intense rain over the tropical southern Africa.…”
mentioning
confidence: 99%